(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Pragmatic competence is an essential aspect of communication that goes beyond grammatical and lexical knowledge. It refers to the ability to use language effectively in various social contexts. In the field of education, particularly in kindergarten settings, educators’ pragmatic competence is critical for fostering an inclusive, supportive, and effective learning environment. This article explores the importance of pragmatic competence in educators, with a focus on the challenges faced by kindergarten teachers who may lack this essential skill. It also highlights how the development of pragmatic competence can improve classroom management, studentteacher relationships, and overall educational outcomes.